Basic ecological analysis of the terrestrial gastropods of the eastern region of San Luis Potosí, Mexico. - Correa-Sandoval, Alfonso; Strenth, Ned E.; Rodríguez Castro, Rubén; Horta Vega, Jorge Víctor (Instituto de Ecología, A.C., 2009)
Of 77 species of terrestrial gastropods found in the eastern region of the state of San Luis Potosí, the ecological conditions supporting the largest number of species of mollusks are as follows: oak forest (44 species), leaf litter and humus (66), soils which are humid throughout the year (53), 3000- 3500 mm annual rainfall (41) and 801-900 m altitude (43). Thysanophora hornii exhibits the greatest distribution with regard to vegetational types, humidity conditions, rainfall, soil types, and altitudinal ranges. The greatest values of diversity and evenness were obtained in the cloud forest (0.6895) and oak forest (0.3512) respectively. The chaparral exhibits the greatest dominance (0.9958) and habitat ecological width (0.3741). Mollusks communities were ecologically ranked lower than the tropical decidouos-subdeciduous forest. The highest qualitative similarity was observed between tropical deciduous-subdeciduous forest and savannah-cultivation (0.7462). The greatest quantitative similarity (0.3646) was observed between thorn forest and savannah-cultivation.